2006
DOI: 10.1016/j.bbmt.2005.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole and Sirolimus Coadministration after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Sirolimus is increasingly used in transplantation for prevention and treatment of graft-versus-host disease and organ rejection. Voriconazole is contraindicated when used concomitantly with sirolimus because of a substantial increase in sirolimus drug exposure with unadjusted dosing, but voriconazole is also considered the best initial treatment of invasive aspergillosis and other fungal infections. Patients who received voriconazole and sirolimus concomitantly were identified by a review of the medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 22 publications
0
60
0
Order By: Relevance
“…15,39,40 The combination of voriconazole and sirolimus is contraindicated according to product information, 41 but sirolimus doses reduced by 70-90% have been used safely in combination with voriconazole. [42][43][44] In our study, no ADE was observed in a patient administered sirolimus (3 mg) as the initial dose, followed by 1 mg every 3 days in combination with voriconazole. Although we found no significant difference comparing the CYA blood concentrations in patients using antimycotics with those who do not, the mean CYA doses were significantly lower (3.1 vs 4.2 mg/kg/d; P ¼ 0.003), reflecting awareness of the potential risk for DDIs.…”
Section: Discussionmentioning
confidence: 47%
“…15,39,40 The combination of voriconazole and sirolimus is contraindicated according to product information, 41 but sirolimus doses reduced by 70-90% have been used safely in combination with voriconazole. [42][43][44] In our study, no ADE was observed in a patient administered sirolimus (3 mg) as the initial dose, followed by 1 mg every 3 days in combination with voriconazole. Although we found no significant difference comparing the CYA blood concentrations in patients using antimycotics with those who do not, the mean CYA doses were significantly lower (3.1 vs 4.2 mg/kg/d; P ¼ 0.003), reflecting awareness of the potential risk for DDIs.…”
Section: Discussionmentioning
confidence: 47%
“…All GVHD prophylaxis regimens were modeled as baseline exposures in the present study, which may have further attenuated the observed sirolimus-tacrolimus protective association for patients in whom sirolimus was subsequently discontinued due to adverse effects, 47 concern for drug interactions, 48 or withdrawal of immunosuppression to increase graft-versus-leukemia effect in cases of relapsed disease. Furthermore, whether the observed association is maintained beyond day ϩ100 was not studied, given the further investment needed for capturing sirolimus exposure later in the transplantation process when GVHD prophylaxis is systematically tapered.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with fluconazole, voriconazole may have greater toxicities [8][9][10] and drug interactions. 11,12 It is unknown if the benefit of voriconazole outweighs these risks.…”
Section: Introductionmentioning
confidence: 99%